Research progress on relationship between N6-adenylate methylation modification and cell transformation and associated mechanism - Zhao ZHAO; Jingjing ZHENG; Mingxuan YANG; Suhua WANG; Xuemin SHI; Yuhang ZHAO (环境与职业医学, 2023)
As a reversible and dynamic epigenetic marker, N6-adenylate methylation (m6A) modification is the most common mRNA modification in eukaryotes. This paper briefly described how m6A can influence RNA splicing, stability, and translation after transcription, and then participate in a variety of signaling pathways and biological and pathological processes, regulating cell proliferation, apoptosis, epithelial mesenchymal transformation (EMT) processes, and tumor invasion and metastasis. In addition, according to current studies, m6A methyltransferases (writers) are believed to promote EMT and tumor development, and readers and erasers both promote and inhibit EMT in different research objects. In this review, we summarized the mechanism of m6A modification and its role in cell transformation, and pointed out the direction of disease treatment.